TRANSFORMASI KELEMBAGAAN KEPEMILIKAN TANAH DESA KLOMPANGAN KABUPATEN JEMBER - Wardhono, Aditya (Jurnal Sosial Ekonomi Pertanian, 2009)
This research is intended to explore pattern of institutional transformation of land ownership in Klompangan Village, Jember Regency in line with the increase of the local development dynamics and the strategy for managing the institutional transformation. Moreover, this article is directed to explore pattern of institutional transformation by considering rural economic actors as the subjects, ignoring whether they are as demand of constituents or supply of institutions. The methodology used in this research was in-depth interview and focus group discussion (FGD) in order to obtain deep information on the process of institutional transformation in every area of the study. The research analysis applied quantitative approach, so it could portray the entire problems of institutional transformation. In institutional transformation of land ownership in Klompangan Village, there was a tendency of pattern transformation of land ownership by villagers as a result of UUPA/1960 penetration. In addition, the land ownership became narrower and narrower that squeezed the ownership due to land transaction reaching 5% of the land owned by out-of-village people. Meanwhile, the handover of land ownership was caused by life need factor, low bargaining position of farmers and urbanization. In other words, the handover of land ownership was prompted by demand of constituents. Keywords: Transformation, Institutional, Land ownership, Rural economy